VIDEO VLOG AS TEACHING MEDIA IN IMPROVING THE STUDENTS’ SPEAKING ABILITY IN PROCEDURE TEXT - Entika Fani Prastikawa; Anisa Juni Fidriani; AB Prabowo Kusumo Adi (Journal of English Education and Linguistics, 2021)
Speaking is one important skill of English to present opinions, ideas, and convey our feeling to other people. Based on my observation teaching practicum in a vocational school, the students speaking ability have less confidence in practicing English speaking. Except for the students’ problem in speaking teacher’s media in the classroom also influence the process of teaching and learning. The use of conventional media is still found in the process of teaching speaking in class. The writer will focus on her research in improving students speaking skills by using media is Vlog. The purpose of this study is 1. To what extent student’s speaking ability taught without using video vlogs in procedure text? 2. To what extent student’s speaking ability taught using vlogs in procedure text? 3. Is there any significant difference between students speaking ability taught using vlogs in procedure text and those taught without using vlogs in procedure text?. The design of this study is quasi-experimental. The data were gathered through quantitative data. The writer takes XI AKL 2 as a control class and XI AKL 1 as an experimental class. The research instrument is a test. There are two types of tests given, namely pre-test and post-test. After collecting data, there are significant differences between the classes taught using video vlogs and the classes taught without video vlog. The results of the study can be seen on the post-test after giving treatment. Were the mean score pre-test was 57.11 which was classified as unsatisfactory and the mean score post-test was 70.67 which was classified as good. The result of the sig 2 tailed was 0.00. If the value of sig ( 2 tailed) < 0.05 then there is a significant difference between the learning outcomes taught without using video vlog between taught using video vlog meanwhile, the value of sig (2 tailed) was 0.000 < 0.005. So it can be concluded that there was a significant difference between the students speaking skills taught using video vlog.